Language, nature and entrapped cognition - Andrey S. Druzhinin (Russian Journal of Linguistics)
As a subfield of ecolinguistics, cognitive ecolinguistics is concerned with the impact of language and cognition on our way and quality of life by approaching language as a medium in and off which a human lives, with which she operates. This paper focuses on linguistically traceable patterns of knowing (perception and thought) that have negative environmental outcomes. It argues that these patterns result from what I call ‘entrapped cognition’ - a human-specific mode of cognition when ways of knowing naturally supersede the known, but at the same time, unnaturally reduce adaptivity to the changing environmental conditions. The study aims to prove that cognitive entrapment is not the fault of the brain or body or environment alone, but rather our brain-body-environment engagement that we harness in and through language. To achieve this aim, I bring methods of systems thinking along to cognitive ecolinguistics and describe four major factors that account for entrapped cognition: a constraint on human agency that creates an illusion of control; the derivative structure of cognition whereby one deals with novelties through older ways of understanding; the observer fallacy by which one phenomenological experience, although occurring post factum, is taken to explain another in hindsight; the confusion of orders of abstraction in understanding experiences due to the ‘sameness’ of linguistic form. An investigation of entrapped cognition in discursive practices reveals four patterns of understanding: traps of allness, stillness, symmetry and sameness. All these ways of cognitive entrapment pose ecological dangers for human flourishing and a healthy, sustainable development of the environment.